Simplifying the Complexity of Machine Translation - Sharp, Randall; Streiter, Oliver (Meta, 1992)
AbstractA description of the CAT2 machine translation system is presented as an example of a model which stresses simplicity over complexity. The design of the formalism encompasses a minimum of formal constructs, yet is powerful enough to describe complex linguistic and translational phenomena. The paper presents an overview of the formalism, followed by examples of its usage in linguistic applications. A critical evaluation is presented, in which the authors discuss the shortcomings of the system and present the directions that are being taken to achieve a more realistic, and more simplified, model of machine translation.